A new High Speed and Accurate FPGA-based Maximum Power Point Tracking Method for Photovoltaic Systems - Adnane Hassani; Mountassar Maamoun; Rezki Tadrist; Ali Nesba (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
We introduce in this paper a new FPGA-based Maximum Power Tracker for photovoltaic systems. The developed approach targets to modify the perturb and observe in view of reaching rapid tracking and achieving excellent accuracy, while keeping the stability performance and the reduced complexity. To perform this improvement, an automatic and smart two steps switcher is integrated, in addition inputs FIR filters are incorporated. Therefore, a high sampling frequency is attained, and consequently the tracking speed is improved. MATLAB simulations and the Xilinx FPGA implementation results show that the improved approach reaches a performance very close to the recently published MPPT methods, with lesser complexity.